2015
DOI: 10.1016/j.virol.2015.03.038
|View full text |Cite
|
Sign up to set email alerts
|

The full-length genome sequences of nine HCV genotype 4 variants representing a new subtype 4s and eight unclassified lineages

Abstract: We characterized the full-length genomes for nine novel variants of HCV genotype 4 (HCV-4), representing a new subtype 4s and eight unclassified lineages. They were obtained from patients who resided in Canada but all had origins in Africa. An extended maximum clade credibility (MCC) tree was reconstructed after the inclusion of 30 reference sequences. It differentiated 18 assigned subtypes and 10 unclassified lineages within HCV-4. Similar analysis of 102 partial NS5B sequences resulted in another MCC tree th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…This Central African region together with the Middle East and Mediterranean regions have been shown to account for the highest number of HCV Genotype 4 infections in the world . There are more than 22 reported subtypes of Genotype 4 and several unassigned lineages . The different subtypes are found in most Central African countries, with somewhat regional differences as predominance of 4h in Burundi and of 4e in Gabon .…”
Section: Discussionmentioning
confidence: 97%
“…This Central African region together with the Middle East and Mediterranean regions have been shown to account for the highest number of HCV Genotype 4 infections in the world . There are more than 22 reported subtypes of Genotype 4 and several unassigned lineages . The different subtypes are found in most Central African countries, with somewhat regional differences as predominance of 4h in Burundi and of 4e in Gabon .…”
Section: Discussionmentioning
confidence: 97%
“…to have a reduced response to DAA treatment in the National Health Service England Early Access Programme in association with the MPRMP NS5A [28][29][30][31][32] amino acid motif that is associated with high-level resistance in vitro. (9,37) In another meta-analysis of patients with genotype 4 infection treated with ledipasvir and sofosbuvir, treatment failure occurred in two thirds of patients with subtype g4r and in one patient with g4b.…”
Section: Discussionmentioning
confidence: 99%
“…The most common genotype detected was g4k, strains of which have been detected in persons across Central Africa (DRC, Republic of the Congo, Central African Republic, Rwanda, Cameroon, and Gabon) and North Africa (Tunisia) and in infected migrants in Europe (United Kingdom, France, and Belgium) and North America (Canada). One Ugandan sequence clustered with the g4s reference sequence (obtained from an unspecified region of East Africa). Three samples (each sequenced on two occasions 6 months apart) clustered within g4v alongside sequences obtained from Rwanda, Burundi, and Cyprus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advances in sequence analysis techniques there has been a dramatic increase in the number of published ORF sequenced HCV isolates, and phylogenetic analysis performed by Smith et al in 2014 confirmed the existence of 7 major genotypes and 67 subtypes [55] (Fig. 1); subsequently a number of additional subtypes have been confirmed [56][57][58]. Subtypes 1a, 1b, 2a, 2b, 2c, 3a, 4a, 4d, 5a and 6a are welldefined worldwide or in specific population groups [59].…”
Section: Phylogenetic Classification Of Hcv Variants Into Highly Divementioning
confidence: 99%